Sustainable Marketing - Themistocleous, Christos (My University, 2023)
This chapter theoretically underpins the term Sustainable Marketing (SM), focuses on its evolutionary pathway, and considers current and future avenues of investigation. Aiming at the enhancement of social, environmental and economic pillars, Sustainable Marketing serves as an integral part of modern CSR practises with Gordon et al. (2011) arguing that Sustainable Marketing is responsible for marketing sustainability. That is, businesses and other actors promoting practises that enhance awareness, trust and understanding while assisting with deviating from apathy on sustainability issues among consumers (p. 145). SM has a structural interactive relationship with consumers (Su et al., 2022) and has evolved from marketers adapting their practices to accommodate emerging ethical needs of consumers to promoting behaviors that heighten sustainability.
Keywords: Sustainability; Marketing; Ethical marketing; Fair Information Practises; Green Marketing